"A Study in Yellow": Investigations in the Stereoselectivity of Ene‐Reductases. (13th October 2021) - Parmeggiani, Fabio; Brenna, Elisabetta; Colombo, Danilo; Gatti, Francesco G.; Tentori, Francesca; Tessaro, Davide
Abstract: Ene‐reductases from the Old Yellow Enzyme (OYE) superfamily are a well‐known and efficient biocatalytic alternative for the asymmetric reduction of C=C bonds. Considering the broad variety of substituents that can be tolerated, and the excellent stereoselectivities achieved, it is apparent why these enzymes are so appealing for preparative and industrial applications. Different classes of C=C bonds activated by at least one electron‐withdrawing group have been shown to be accepted by these versatile biocatalysts in the last decades, affording a vast range of chiral intermediates employed in the synthesis of pharmaceuticals, agrochemicals, flavours, fragrances and fine chemicals. In order to access both enantiomers of reduced products, stereodivergent pairs of OYEs are desirable, but their natural occurrence is limited. The detailed knowledge of the stereochemical course of the reaction can uncover alternative strategies to orient the selectivity via mutagenesis, evolution, and substrate engineering. An overview of the ongoing studies on OYE‐mediated bioreductions will be provided, with particular focus on stereochemical investigations by deuterium labelling. Abstract : "Elementary, Watson!" The recent efforts to investigate and understand the stereochemical course of the asymmetric bioreduction of C=C bonds mediated by ene‐reductases are reviewed, covering the literature of the last two decades. A general binding model is presented and successful approaches to stereodivergent reductions are discussed with representative examples.